2020
DOI: 10.3233/jad-200306
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids and Lipopolysaccharide as Mediators Between Gut Dysbiosis and Amyloid Pathology in Alzheimer’s Disease

Abstract: Background: Metagenomic data support an association between certain bacterial strains and Alzheimer’s disease (AD), but their functional dynamics remain elusive. Objective: To investigate the association between amyloid pathology, bacterial products such as lipopolysaccharide (LPS) and short chain fatty acids (SCFAs: acetate, valerate, butyrate), inflammatory mediators, and markers of endothelial dysfunction in AD. Methods: Eighty-nine older persons with cognitive performance from normal to dementia underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(147 citation statements)
references
References 85 publications
4
142
0
1
Order By: Relevance
“…They can interfere with various Aβ peptides, thereby potently inhibiting Aβ fibril aggregation in vitro (Ho et al, 2018), possibly reducing the accumulation of neurotoxic oligomers in the brain. Marizzoni et al (2020) reported a novel association between gut microbiota-derived SCFAs and systemic inflammation with brain amyloidosis via endothelial dysfunction in a clinical study. Erny et al (2015) also suggested that SCFAs may help modulate the maturation and function of microglia in the brain.…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…They can interfere with various Aβ peptides, thereby potently inhibiting Aβ fibril aggregation in vitro (Ho et al, 2018), possibly reducing the accumulation of neurotoxic oligomers in the brain. Marizzoni et al (2020) reported a novel association between gut microbiota-derived SCFAs and systemic inflammation with brain amyloidosis via endothelial dysfunction in a clinical study. Erny et al (2015) also suggested that SCFAs may help modulate the maturation and function of microglia in the brain.…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…All species within the phylum Bacteroidetes are gram-negative and contain the toxin LPS in their outer membrane ( 15 , 24 , 25 ). Higher circulating levels of LPS were associated with increased Aβ deposition in elderly patients with cognitive complaints ( 62 ). Increased abundance was detected in most genera within Bacteroidetes and most of its species, including B. fragilis ( 60 ), which produces polysaccharide A (PSA) ( 7 ).…”
Section: Microbiota Composition In Ad Patients and Ad Animal Modelsmentioning
confidence: 99%
“…At species level, butyrate-producers like R. hominis , F. prausnitzii, E. rectale and E. hallii were lower abundant in AD patients ( 60 ). Interestingly, butyrate levels in plasma negatively associated with Aβ deposition in cognitively impaired patients ( 62 ).…”
Section: Microbiota Composition In Ad Patients and Ad Animal Modelsmentioning
confidence: 99%
“…They are also referred to as friendly or healthy bacteria supplied through foods, beverages, and dietary supplements. One of their reported benefits has been associated with anti-inflammatory effect [ 12 ] and correction of gut microbiota dysbiosis [ 13 ], that is proposed to be a driver of inflammation and recently shown to correlate with amyloid deposition in the brain of living subjects suffering from AD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%